Food as a protective factor against Alzheimer's disease (Research, Society and Development, 2020)
Alzheimer's disease (AD) is characterized as a neurodegenerative syndrome that leads to loss of cognitive functions and causes progressive impairment of day-to-day activities. Studies have shown that eating can have a neurological protective effect and reduce the risk of developing AD. The objective of this study was to present the main nutrients involved in the protection of AD. The main nutrients associated with AD prevention identified in this study are the B vitamins, vitamin C, D and E, omega 3 and selenium. The protection mechanisms of these nutrients against dementia and delayed cognitive decline are associated with their antioxidant power, role in the functioning of neurotransmitters, decreased homocysteine ​​levels, among others. It was observed the importance of early nutritional intervention in the management of AD, the monitoring of AD patients with a multidisciplinary team, as well as the use of specific methods of nutritional diagnosis in order to prevent the effects of AD.